TEACHER’ PERSPECTIVE OF ENGLISH MATERIAL FOR TOURISM INDUSTRY PROGRAM IN SMKN 4 SAMPIT - Sholichah, Nikmatus; Bahing, Bahing; Ristati, Ristati (Journal Compound: Improving the Quality of English Education, 2021)
Vocational High School was designed to prepare the students to be ready to work after they graduate. In Vocational High School, students must have an appropriate competence based on their major. English becomes very important in this school since most of jobs in the workplace put English proficiency both written and spoken. Giving materials in Vocational High School must be appropriated to the students’ needs for their work place future. Module becomes one of effective media in teaching learning, the statement above was strengthened by Mayer’ theory in Lasmiyati (2014) stated that module is relatively short self-contained independent unit of instructional designed to achieve a limited set of specific and well-defined educational objectives. This research aimed to analyze the students’ perspective toward implementation of ESP module for Tourism Industry students in English teaching learning. This research was a qualitative descriptive, the online interview sheet that form of google form used as a research instrument in collecting data. The data analyzed qualitatively by explaining the result descriptively. The findings showed that the English book used in SMKN 4 sampit was too general. And the English teacher who tough in Tourism Industry Program found difficulty of English teaching that related to the English materials. The next finding showed that, the English skills were most be needed by the Tourism Industry students were speaking and writing. And the result suggested that the English materials in Tourism Industry Program in SMKN 4 Sampit sould be developed based on syllabus used and students’ needs.